Gender Empowerment in Black Widow (2021) - Nur Hidaya (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
Gender empowerment has become one of the ways to deal with gender issues in the era of discrimination and patriarchy in gender-based life. The gender empowerment movement is a global movement that promotes women's rights by making various breakthroughs. This study aims at how gender empowerment is represented, the impact of gender empowerment and its contribution to reducing discrimination in social life so that gender equality which is the main goal of gender empowerment, can be achieved. In this study, the researcher used a feminist approach in analyzing Black Widow (2021) as data, leading to literary works representing women's daily problems. The feminist view does not limit itself to analyzing the work's aesthetic value but instead considers the significance of the relationship between social and cultural contexts. The author concludes that this research helps change cultural representations of women who always look down on women in films in future films and real life, that women can do anything just like men with gender empowerment. Keywords: Discrimination, Exploitation, Gender Empowement.